2015
DOI: 10.1073/pnas.1502281112
|View full text |Cite
|
Sign up to set email alerts
|

Highly compacted biodegradable DNA nanoparticles capable of overcoming the mucus barrier for inhaled lung gene therapy

Abstract: Gene therapy has emerged as an alternative for the treatment of diseases refractory to conventional therapeutics. Synthetic nanoparticle-based gene delivery systems offer highly tunable platforms for the delivery of therapeutic genes. However, the inability to achieve sustained, high-level transgene expression in vivo presents a significant hurdle. The respiratory system, although readily accessible, remains a challenging target, as effective gene therapy mandates colloidal stability in physiological fluids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 65 publications
5
156
0
1
Order By: Relevance
“…We have previously demonstrated that muco-inert nanoparticles capable of efficiently penetrating airway mucus provide widespread in vivo distribution throughout the mouse airways following inhalation, whereas muco-adhesive nanoparticles were unable to do so (28,29). We thus investigated the airway distribution of Cy5-labeled FTn, with or without PEG surface coatings, following intranasal administration in mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that muco-inert nanoparticles capable of efficiently penetrating airway mucus provide widespread in vivo distribution throughout the mouse airways following inhalation, whereas muco-adhesive nanoparticles were unable to do so (28,29). We thus investigated the airway distribution of Cy5-labeled FTn, with or without PEG surface coatings, following intranasal administration in mice.…”
Section: Resultsmentioning
confidence: 99%
“…The sections were stained with Prolong Gold antifade with DAPI (Life Technologies), and fluorescence images of the sections were obtained using a Zeiss confocal microscope. To quantify the particle distribution, the acquired images were analyzed by following an image-based analysis method that we have previously reported (28). Briefly, at least 10 fluorescence images at 10× magnification were taken of the lungs harvested from individual animals.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, mucus buildup is often associated with inflammation, which can lead to reduced efficacy of viral vectors when they are taken up by an increased number of resident lung macrophages, attracted by a boosted immune system. Both these issues can possibly be overcome by mucus-penetrating nanoparticles, or the co-administration of mucolytic drugs [45]. …”
Section: A Brief History Of In-vivo Gene Therapymentioning
confidence: 99%
“…18,49 Most nonviral gene vectors are formulated with positivelycharged carrier materials, including cationic polymers and lipids, that condense nucleic acids into NP with net positively-charged surfaces. [79][80][81][82] Sanders et al, showed the diffusion of cationic 1,2-dioleoyl-3-trimethylammoniumpropane (DOTAP) lipoplexes was strongly hindered in CF mucus. 79 This effect was also observed for some polymer-based gene delivery systems, including those made using polyethylenimine, 80 polyamidoamine dendrimer, 81 and poly-β-amino ester, 82 each of which also carry positively-charged surfaces (>20 mV ζ-potential).…”
Section: Trapping Mechanismsmentioning
confidence: 99%